2006
DOI: 10.1111/j.1365-2613.2006.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental abnormalities in multiple proliferative tissues of ApcMin/+ mice

Abstract: Germ-line mutation of the Apc gene has been linked to familial adenomatous polyposis (FAP) that predisposes to colon cancer. Apc(Min/+) mice, heterozygous for the Apc gene mutation, progressively develop small intestinal tumours in a manner that is analogous to that observed in the colon of patients with FAP (Su et al. 1992; Fodde et al. 1994; Moser et al. 1995). We have studied the effects of Apc gene mutation on murine intestinal and extra-intestinal, proliferatively active tissues. We have contrasted the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 27 publications
(65 reference statements)
4
55
0
Order By: Relevance
“…Although deletion and duplication of the APC has been associated with testicular dysgenesis syndrome (TDS) and other testicular abnormities (48), its loss in SCO has heretofore not been described. Additionally, mutations and hypermethylation of the APC gene has been observed in human testicular yolk sac tumor patients (2), and a progressive decrease in male fertility was noted in APC min/ϩ mice, a well-studied mouse model of colon cancer (49). However, the mechanisms involved in APC-mediated infertility were not reported.…”
Section: Discussionmentioning
confidence: 97%
“…Although deletion and duplication of the APC has been associated with testicular dysgenesis syndrome (TDS) and other testicular abnormities (48), its loss in SCO has heretofore not been described. Additionally, mutations and hypermethylation of the APC gene has been observed in human testicular yolk sac tumor patients (2), and a progressive decrease in male fertility was noted in APC min/ϩ mice, a well-studied mouse model of colon cancer (49). However, the mechanisms involved in APC-mediated infertility were not reported.…”
Section: Discussionmentioning
confidence: 97%
“…We first tested whether chronically administered zebularine could prevent or delay tumor progression in Apc Min/+ (Min) mice. Min mice have a nonsense mutation in the adenomatous polyposis coli (Apc) gene, which leads to the development of multiple adenomas in the intestines along with other phenotypes such as anemia, splenomegaly, and impaired development of proliferative tissues (19)(20)(21). We found that oral administration of zebularine resulted in decreased tumorigenicity.…”
mentioning
confidence: 86%
“…and treated males at the time of euthanasia (21). However, a significant decrease in the weight and size of spleen was noted in the treated female group (P = 0.0004; Supplementary Fig.…”
Section: Effects Of Chronic Zebularine Administration In Min Micementioning
confidence: 96%
“…Min/+ mice undergo thymic atrophy and splenomegaly with lymphodepletion as well as loss of Peyer's patches accompanying intestinal tumorigenesis (17,18). It has also been reported that the rapid onset of tumors in the intestine coincides with the loss of thymus (15).…”
Section: Il-17a Ablation Corrected Immune Abnormalities It Has Been mentioning
confidence: 99%